The anti‐adhesive effect of thermally cross‐linked gelatin film and its influence on the intestinal anastomosis in canine models122. Issue 1 (17th October 2012) - Tsujimoto, Hiroyuki; Tanzawa, Ayumi; Matoba, Mari; Hashimoto, Ayumi; Suzuki, Shuko; Morita, Shinichiro; Ikada, Yoshito; Hagiwara, Akeo
Abstract: To generate a more effective and safer anti‐adhesive material, we have developed a new type of thermally cross‐linked gelatin film. In this study, we preclinically examined the anti‐adhesive efficacy of this film and evaluated the possibility applying the film safely onto fresh intestinal anastomoses, compared with hyaluronate and carboxymethyl‐cellulose (HA/CMC) film. Using a canine adhesion model, the degree of adhesion for each film was evaluated by adhesion scoring systems and histological observation. Three weeks after surgery, only the gelatin film showed significantly superior anti‐adhesive effects compared to the control (no treatment), in particular, exhibiting excellent re‐peritonization. Next, in a canine anastomosis model, the anastomoses were wrapped directly by each film and the bursting pressures of the anastomoses were examined 3 and 7 days after surgery. The gelatin film did not significantly affect either the bursting pressures or the healing process, compared with the control. However, the HA/CMC film significantly decreased the bursting pressures measured at 3 days after surgery. In conclusion, the thermally cross‐linked gelatin film had satisfactory anti‐adhesive effects with excellent re‐peritonization. It could be safely applied to intestinal anastomoses without decreasing the bursting pressures. The gelatin film is considered to be quite favorable as an anti‐adhesive material. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 99–109, 2013.